2018
DOI: 10.1038/s41598-018-29729-4
|View full text |Cite
|
Sign up to set email alerts
|

A Gustatory Receptor Used for Rapid Detection of Tyrophagus putrescentiae in Fungi Hosts

Abstract: The storage mite, Tyrophagus putrescentiae, found worldwide in many habitats, is an important pest of edible fungi in China. Storage mites are tiny and difficult to observe, especially when they occur in fungi composts. In this study, one gustatory receptor protein (TputGR1) was identified from the transcriptome of T. putrescentiae. Phylogenetic analysis of GRs families from 10 arthropod species revealed that TputGR1 had high homology with the SccaGR1 of Sarcoptes scabiei and TurtGR1-2 of Tetranychus urticae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…There are 68 GRs in D. melanogaster , 90 in Anopheles gambiae , 107 in Aedes aegypti and 126 in Culex quinquefasciatus 52 . Similarly, among different mites, 54 and 21 GRs are found in Metaseiulus occidentalis and Ixodes scapularis , respectively 53 . Phylogenetic analysis has shown that there are conserved orthologs of sugar, carbon dioxide and several orphan receptors between mosquitoes and D. melanogaster 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are 68 GRs in D. melanogaster , 90 in Anopheles gambiae , 107 in Aedes aegypti and 126 in Culex quinquefasciatus 52 . Similarly, among different mites, 54 and 21 GRs are found in Metaseiulus occidentalis and Ixodes scapularis , respectively 53 . Phylogenetic analysis has shown that there are conserved orthologs of sugar, carbon dioxide and several orphan receptors between mosquitoes and D. melanogaster 54 .…”
Section: Discussionmentioning
confidence: 99%
“…52 Similarly, among different mites, 54 and 21 GRs are found in Metaseiulus occidentalis and Ixodes scapularis, respectively. 53 Phylogenetic analysis has shown that there are conserved orthologs of sugar, carbon dioxide and several orphan receptors between mosquitoes and D. melanogaster. 54 For example, AaGR34 and AgGR25 are orthologs of DGR43a.…”
Section: Mode Of Actions and Molecular Sensors Of Ir3535mentioning
confidence: 99%